Effect of Lifting Time and Drying Method on Yield, Quality and Aspergillus Flavus Incidence on Rainfed Groundnut - Osman and Mohamed EIFatih, Abdelrahman K. (Gezira Journal of Agricultural Science, 2021)
Two experiments were conducted over a period of five years from 1985  to 1 989, at Elobeid Agricultural Research Station Farm to study the effect of lifting time and drying method on yield, grade, kernel moisture content and aflatoxin incidence of rainfed groundnut. A randomized complete block design with three replications was used. Seven lifting times were made at 10-day intervals, staffing at 80 days and continuing up to 140 days after planting. Four drying methods were tested, two traditional ones, in which the plants were stacked with pods placed in the centre of the heap or packed over each other, and the other two included inverted windrows with pods upward and a new suggested method in which plants were stacked with pods placed up exposed to direct sunlight and air current. Lifting time significantly (P=0.05) affected yield and its grade. Early lifting increased the percentage of immature pods and resulted in low yield of poor grade, while late lifting increased the underground losses and decreased intact yield. Significant (P=0.05( positive correlation was found between lifting time and pod infection with A. flavus . Higher A. flavus infection was observed at late lifting. The results of the drying method experiment indicated that the level of aflatoxin contamination varied from one season to another. In the new suggested method and the inverted windrow method, the drying rate is faster and the percentage of contaminated samples was lower than that of the two traditional drying methods. To obtain high intact yield of good grade and reduced aflatoxin contamination, it is recommended to lift the crop at 100-110 days from planting and dry it for 8 days by stacking the plants with pods placed upward, so as to expose the pods to direct sun-light and air current.